2022
DOI: 10.30773/pi.2021.0094
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Steroid Hormones, Genes Related to Testosterone Metabolism and Behavior in Boys With Autism in Slovakia

Abstract: sis of autism and fetal testosterone levels were positively correlated with autistic traits in general population. [1][2][3][4] In addition, females with conditions of abnormal prenatal exposure to testosterone and its sex steroid precursors, such as congenital adrenal hyperplasia and polycystic ovary syndrome, were found to have higher rate of autistic traits as well as their children were of higher risk of developing autism. 5,6 However, the exact mechanism by which these hormones influence the manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…ASD has been associated with altered circulating steroid hormones levels (e.g., testosterone, cortisol, estradiol) [27,[44][45][46][47][48][49][50][51][52]. We did not observe any effects on circulating testosterone levels or testosteroneassociated behaviors (e.g., aggression) in offspring exposed to gestational CIH.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…ASD has been associated with altered circulating steroid hormones levels (e.g., testosterone, cortisol, estradiol) [27,[44][45][46][47][48][49][50][51][52]. We did not observe any effects on circulating testosterone levels or testosteroneassociated behaviors (e.g., aggression) in offspring exposed to gestational CIH.…”
Section: Discussionmentioning
confidence: 55%
“…Differences in steroid hormones, (e.g., testosterone, cortisol, estrogen) during gestation and later in life may also contribute to the phenotype of ASD [44][45][46][47][48]. The intensity of social impairments, repetitive behaviors, and precocious puberty in ASD has been correlated to testosterone and estradiol levels [27,49,50]. Further, elevated diurnal cortisol may contribute to comorbid anxiogenic conditions [51,52].Since gestational hypoxia can have a long-lasting impact on offspring physiology, brain function, and behavior, it is important to understand the in uence of sex and age on gestational hypoxia-associated chronic outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sanger Sequencing or ARMS PCR). There are variations in genes previously strongly associated with ASD such as SLCO1B1 26 , ACADSB 27 , TCF4 28 , HCP5 29 , MOCOS 30 , SRD5A2 31 , MCCC2 32 , DCC 33 and PRKN 34 . The ratio of males/ females among the samples with identified mutations is 3.93 (Sup.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 ). In terms of SRD5A2 , a recent study found that ASD boys with rs9282858 mutation in this testosterone metabolism-related gene showed higher levels of restricted and repetitive behaviors 31 . In addition, multiple recent studies published on Clinvar have consistently concluded SRD5A2 rs9332964 as pathogenic/likely pathogenic.…”
Section: Discussionmentioning
confidence: 99%